Flow perturbation measurements by numerical analysis of the power spectrum of a doppler signal - PIECHOCKI, Maciej (Archives of Acoustics, 1985)
A method was elaborated to measure flow perturbations. It was based on analysis of the power spectrum of a Doppler signal. In view of the simplifications assumed, it concerns pulsed flowmetres. The process of the formation of the Doppler signal is described mathematically, its power spectrum is calculated. A numerical model of the signal power spectrum is prosecuted. It has been constructed to calculate the effect of the gradient of the mean velocity in the sample volume, and also to determine the effect of the passage of blood particles through the sample volume on the shape of the power spectrum.This model was verified experimentally. On the basis of it, a corrected turbulence index was proposed. This index describes with greater precision the flow perturbations.